Treino de relações intraverbais e implicações para a reversibilidade da relação - Santos, Maxleila Reis Martins (2006)
Intraverbal is a verbal operant in which a verbal stimulus is the occasion for a particular verbal response - with no point-to-point correspondence to the verbal stimulus that evoked it - to be emitted, and that response is maintained by a generalized reinforcement stimulus. Translation is a special case of intraverbal behavior, in which stimuli are in one language and responses are in another. When two languages are acquired independently there may be little intraverbal connections between them. The aim of this work was to investigate (a) the production of intraverbal behavior involving pairs of words in Portuguese-English and English-Portuguese, (b) how the establishment of these pairs would influence the acquisition of new intraverbal behavior with similar characteristics to those already produced, and (c) whether the training that promotes the acquisition of an intraverbal - for example, stimulus-word-in-Portuguese and response-word-in-English - would suffice to produce the emergence of another corresponding intraverbal in the opposite direction. Eleven participants, whose native language was Portuguese and with little or no knowledge of English, concluded the study. In a trial-and-error procedure, each participant realized a task in the computer which consisted of typing the translation for a word shown in the center of the screen. If the stimulus-word was in English, a response in Portuguese was demanded, and vice-versa. When the stimulus-word was shown, the participant could ask for hints (pressing tab or enter), and it was up to him/her to end the attempt once he/she considered it finished, at which moment a message would indicate a hit or miss. Typing errors at each letter were shown as well. In each experimental stage, the same set of words was presented in random order, half of them being in Portuguese and half in English. Once the set of words was finished, it was re-presented until the participant met the criterion for completion of that stage. This procedure involved 4 experimental phases: on Phase 1 a set of 20 words was presented; on Phase 2 the direction of the training was inverted - words presented in English on Phase 1 were presented in Portuguese and vice-versa. On Phase 3, a new set of 10 words was presented, and Phase 4 consisted of the inversion of that set. Results indicate that more training was necessary in order to obtain some precision in the establishment of intraverbal relations in which the stimulus-word was in the participants' native language and the response-word was in foreign language, at least when words are presented in written dimension and responses are demanded in the same dimension. Results also indicate that reversibility cannot be expected, since in many cases the training in one direction did not suffice for the intraverbal relationship to remain intact when what was previously a response-word became a stimulus-word and vice-versa. Results show, however, that intraverbal training which presents stimulus-words in one language and demands as a response the emission of a word in another language has some effect over the participants' performance when the inverse intraverbal, or even new intraverbals with other pairs of words, are demanded. However, this effect may be quite different, depending on the initial direction of the training - initial training based on stimulus-words in the native language and response-words in the foreign language though apparently more difficult at first, made the emission of the intraverbal chain more probable when those words were inverted. The role of diverse behavioral histories (familiarity) with words in one language and previous knowledge of the second language, as well as characteruistics of individual words and of sub-set of words are discussed as relevant variables in determining performance